Transsphenoidal Removal of Retroclival Chondroma with Pituitary Transposition Manifesting as Repeated Subarachnoid Hemorrhage: A Case Report - Ogawa, Yoshikazu; Niizuma, Kuniyasu; Tominaga, Teiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Intracranial chondromas are extremely rare and represent only 0.2% of all intracranial primary neoplasms. The histologic appearance lacks nuclear atypism and mitoses, and it usually shows low growth potential, although these benign features do not necessarily imply a good prognosis.Case Description A 44-year-old man was referred to our institution with a subarachnoid hemorrhage (SAH). He had a history of SAH 5 years previously that was diagnosed as unknown etiology at another hospital. Head magnetic resonance imaging showed a large tumor located in the prepontine cistern and extending up to the interpeduncular cistern, and the tumor was irregularly enhanced with contrast medium. Retrospective analysis of the original computed tomography of 5 years earlier identified a small contrast enhancing defect behind the dorsum sellae. Tumor removal was planned to prevent repeated SAH and control the apparently growing tumor. An extended transsphenoidal approach was performed. The pituitary gland was dissected from the bottom of the sellar floor and transposed forward to the prechiasmatic cistern with preservation of the pituitary stalk and its blood supply, and subtotal removal of the tumor was achieved. Postoperative diabetes insipidus disappeared within a few days, and the patient was discharged without neurologic or endocrinologic deficits. Histologic examination established the diagnosis as chondroma without a sarcomatous component. Follow-up examination 3 months after surgery showed a re-enlargement of the residual tumor, and gamma knife surgery was performed.Conclusions Intracranial chondroma sometimes manifests as intracranial hemorrhage and grows comparatively rapidly in a short period despite the benign histologic features. A long and careful follow-up period is essential.
Keywords: chondroma; extended transsphenoidal approach; pituitary transposition; subarachnoid hemorrhage